Mechanisms of Tolerance: Role of the Thymus and Persistence of Antigen in Calcineurin-Induced Tolerance of Renal Allografts in MGH Miniature Swine - Scalea, Joseph R.; Hanekamp, Isabel; Yamada, Kazuhiko (IntechOpen, 2011)
None